Interfunctional coordination and its influence on customer success - Eva Tomaskova (Open Economics, 2018)
The purpose of the paper is to expand the knowledge about interfunctional coordination (IFC). The term IFC has been used for 50 years and it extends to many branches. The most popular ones are in marketing, logistics and IT management. The purpose of IFC is to develop collaboration between the diverse departments within an organization. The goal of the paper is to describe the relationship between IFC on the B2B market, especially if IFC in one company can influence customer success in business. The research was undertaken with companies producing electronic components and electrical equipment in the region of South Moravia in the Czech Republic. 60 SME have answered the questionnaire. The Spearman's rank correlation test was used to analyse the influence of IFC of companies on the success of their customers. The results show that the implementation of IFC in a company has a positive relationship on the success of its customers.
Keywords: M10; M31; 330; business performance; customer success; Czech Republic; Interfunctional coordination; market orientation